2022
DOI: 10.1002/oby.23440
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiometabolic disease severity, social determinants of health (SDoH), and poor COVID‐19 outcomes

Abstract: Objective Determine the ability of retrospective cardiometabolic disease staging (CMDS) and social determinants of health (SDoH) to predict COVID‐19 outcomes. Methods Individual and neighborhood SDoH and CMDS clinical parameters [BMI, glucose, blood pressure, HDL, triglycerides], collected up to 3 years prior to a positive COVID‐19 test, were extracted from the electronic medical record. We used Bayesian logistic regression to model CMDS and SDoH to predict subsequent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…It is well known that sustained, chronic stress has several deleterious effects on normal physiology. It sets off a chain reaction within the body, sparking inflammatory responses and prompting intricate alterations in gene expression, known as epigenetic modifications 44 . These modifications, in turn, have the potential to significantly impact health outcomes, potentially worsening the long-term effects of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that sustained, chronic stress has several deleterious effects on normal physiology. It sets off a chain reaction within the body, sparking inflammatory responses and prompting intricate alterations in gene expression, known as epigenetic modifications 44 . These modifications, in turn, have the potential to significantly impact health outcomes, potentially worsening the long-term effects of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with the results of the present study. BMI is associated with unfavorable SDoH in developed countries [36,37] . However, the Chinese Longitudinal Healthy Longevity Survey showed that patients with low BMI had more unfavorable SDoH [38] , which is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that sustained, chronic stress has several deleterious effects on normal physiology. It sets off a chain reaction within the body, sparking in ammatory responses and prompting intricate alterations in gene expression, known as epigenetic modi cations 40 . These modi cations, in turn, have the potential to signi cantly impact health outcomes, potentially worsening the long-term effects of COVID-19.…”
Section: Disease Severitymentioning
confidence: 99%